PENDAMPINGAN LEGALITAS USAHA UNTUK MENINGKATKAN KUALITAS DAN KUANTITAS PENJUALAN UMKM SIKEYYAN DI DESA BEGED, KECAMATAN GAYAM, KABUPATEN BOJONEGORO - Elvania, Nindy Callista; Rohmah, Siti; Fatimah, Siti; Sintia, Sintia; Tria Desinta, Silvia Ayu (Jurnal Abdi Masyarakat, 2023)
Sikeyyan is a Micro, Small and Medium Enterprise in Beged Village, Gayam District, Bojonegoro Regency. These Micro, Small and Medium Enterprises do not yet have business legality in general in the form of NIB, PIRT, trademarks and halal certificates. This is what makes intestinal chips products not very well known among the public. From this problem, we aim to provide assistance on the legality aspect of business by providing facilitation and guidance regarding the requirements in managing business legality that must be owned by business actors. The method used in assisting business legality is PAR (Participatory Action Research). PAR has three words that are always related to one another, namely participation, research, and action. All research must be implemented in action. PAR-based research is designed to examine something in order to change and make improvements to it. This assistance provides thebenefit of increasing the quality and quantity of sales of Sikeyyan MSME.